DETERMINATION OF GRAY ZONE RANGE IN HBsAg TEST AND ITS IMPLICATION FOR HBsAg CONFIRMATION TEST - Vina Zakiah Latuconsina; Irda Handayani; Asvin Nurulita; Uleng Bahrun (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Hepatitis is an inflammation of liver cells caused by infection (virus, bacteria, paracytes), medication, alcohol consumption, excessive lipid and autoimmune disease. Increasing method (sensitivity) of HBsAg test is often followed by a lot of false positive test results, which need a confirmation test which takes a longer time and higher cost so that it is needed to determine an optimal gray zone range for a confirmation test. This analytical cross-sectional study was held at the Clinical Pathology Laboratory of the Dr.Wahidin Sudirohusodo Hospital Makassar. The subjects were specimens which HBsAg value was within 0.06-1 COI. Specimens were examined using HBsAg confirmation test. Over 49 samples collected there were 32 reactive and 17 non-reactive. 14 out of 32 reactive samples (43.8%) were confirmed as negative (false positive) by HBsAg confirmation test and 3 out of 17 non-reactive samples (17.6%) were confirmed as positive (false negative). Chi-square test showed a significant correlation between HBsAg value and HBsAg confirmation test value (p=0.009). Chi-square test with some intervals with α=1% showed that the interval of HBsAg value 0.13-0.17 COI was the interval with the lowest significant value (p=0.004). This subsequent interval was recommended as the gray zone range. The range 0.13-0.17 was most optimal as HBsAg gray zone to determine the need for a confirmation test. A further study with larger samples is suggested.